2020
DOI: 10.18332/tpc/125915
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Tobacco-Free Campus: A Survey of Student Attitudes, Opinions, and Behaviors

Abstract: INTRODUCTION The effectiveness of tobacco-free campus policies in preventing and mitigating tobacco use relies on students' perceptions, opinions, and adherence to clean-air restrictions. The purpose of this study was to gather data regarding student attitudes, opinions and tobacco use behaviors, one year following implementation of the tobacco-free campus initiative. METHODS Data were gathered using an anonymous, online survey of graduate and undergraduate students at a public university, one year following i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, there are practical difficulties in this regard. A study by Pignataro and Daramola (2020) reported that college students replaced tobacco with vaping, using electronic cigarettes, and using hookahs [8]. The study revealed that the students had a less favorable position when discussing a ban on electronic cigarettes and smokeless tobacco than conventional tobacco products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are practical difficulties in this regard. A study by Pignataro and Daramola (2020) reported that college students replaced tobacco with vaping, using electronic cigarettes, and using hookahs [8]. The study revealed that the students had a less favorable position when discussing a ban on electronic cigarettes and smokeless tobacco than conventional tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, young adults comprise the greatest proportion of e-cigarette users [5,7]. According to the Substance Abuse and Mental Health Services Administration (SAMSHA), college students have the highest tobacco usage rates, with a prevalence of 20% or more among this population [8,9]. The 2017 Monitoring the Future survey among youth found that 7.4% vaped nicotine, 3.6% vaped marijuana, and 8% vaped for flavor [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the American College Health Association advocated for a 100% tobacco-free environment [ 6 , 8 ], the tobacco-free campus (TFC) policy has been hailed as the most advanced tobacco-control strategy on college campuses. TFC refers to colleges and universities that have completely banned all types of tobacco products for both indoor and outdoor environment and the ban includes smokeless tobacco, whereas smoking bans restrict cigarette smoking only [ 9 ]. Enforcement of a TFC policy has been known to reduce smoking rates, the risk of exposure to secondhand smoke [ 10 ], and the use of alternative tobacco products [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As of July 2020, at least 2,511 United States and Tribal universities declared smoke‐free and/or tobacco‐free policies, 2,076 (83%) of which placed additional bans on noncombustible product substitutes (e.g., electronic cigarettes; American Nonsmokers' Rights Foundations, 2022; Wang et al, 2018). Campus tobacco‐policy research explores barriers and facilitators of policy implementation (e.g., Hellesen et al, 2022; Lee et al, 2015), acceptance of policies by the general public (e.g., Braverman et al, 2021; Mamudu et al, 2012; Pignataro & Daramola, 2020), and methods for measuring policy compliance (e.g., Fallin et al, 2014; Russette et al, 2014). Relatively few studies have objectively measured behavior change following tobacco policy enactment, and only a small sample of the reports describe efforts to observe smoking directly (e.g., Fitzpatrick et al 2009; Gatto et al, 2019; Harris et al, 2010).…”
mentioning
confidence: 99%